PERAN PENYIDIK PANGKALAN TNI ANGKATAN LAUT DALAM PENANGGULANGAN PENCURIAN IKAN OLEH KAPAL IKAN ASING DI PERAIRAN NATUNA - Arcan, Rama (UNES Law Review, 2021)
Law Number 17 of 1985 concerning Ratification of the United Nations Convention on the Law of the Sea 1982 (UNCLOS 1982). Indonesia has sovereign rights to utilize, conserve and manage fish resources in the Indonesian Exclusive Economic Zone (ZEEI) and the high seas. The large number of natural resources contained in the sea makes it vulnerable to illegal exploitation and exploration by irresponsible parties. Anambas Islands Regency has a total of 255 islands located in the Natuna waters, the Tarempa Navy Base (Lanal) often gets foreign-flagged fishing boats caught illegally stealing fish caught carrying out patrols in the Natuna waters.